Reds and blues - Hunt, Roderick; Brychta, Alex. (Oxford : Oxford University Press, 2004)
This series are large format version of the storybooks. They are suitable for whole class teaching and group work to encourage the children to talk about the stories.
Stage 1+ First sentences.
K-3.
English.
Keywords: Colour -- Fiction; Football -- Fiction; Reading training, English